Subconsciousness : automatic behavior and the brain - Agid, Yves (Columbia University Press, 2021)
"We are conscious of only a small fraction of our lives. Because the brain constantly receives an enormous quantity of information, we need to be able to do things without thinking about them-to act in "autopilot" mode. Automatic behaviors-the vast majority of our activities-occur without our conscious awareness, or subconsciously. Yet the physiological basis of subconsciousness remains poorly understood, despite its vast importance for physical and mental health. The neurodegenerative disease expert Yves Agid offers a groundbreaking and accessible account of subconsciousness and its significance. He pinpoints the basal ganglia-the ancient "basement of the brain"--As the main physiological hub of the subconscious. Agid examines its roles in the control and production of automatic behavior, including motor, intellectual, and emotional processes. He highlights the consequences for various brain pathologies, showing how malfunctions of the subconscious have clinical repercussions including not only abnormal involuntary movements, as seen in Parkinson's disease, but also psychiatric disorders such as obsessive-compulsive disorders and depression. Based on this understanding, Agid considers how seeing the basal ganglia as a therapeutic target can aid development of potential new treatments for neurological and psychiatric disorders. Shedding new light on the physiological bases of our behavior and mental states, this book provides an innovative exploration of the complexities of the mind, with implications ranging from clinical applications to philosophy's thorniest problems"--